Biochemical Markers of COVID -19: Role in Diagnosis, Management and Predicting Severity of the Disease - BHAT, KIRAN; Ahmad, Sohaib (International Journal of Innovative Research in Medical Science, 2023)
The emergence of variants of corona which are getting transmitted easily and are more virulent and fatal has made things more difficult and the need to know about the prognostic markers has taken a priority besides vaccination. All COVID-19 RT PCR positive patients were categorized into mild, moderate and severe category any time during hospital stay based on the WHO guidelines 2021. Comparison of all clinical and selected biochemical parameters (Ferritin, LDH, IL-6, TLC, NLR, albumin, D-dimer and procalcitonin) was done. The Aim of the study was to establish a cut off level of the biomarkers of COVID -19 which could determine the severity of the disease and act as prognostic factors too. These biochemical markers include NLR, serum D-dimer, CRP, IL-6, ferritin, LDH, albumin, procalcitonin, AST and ALT(p<0.001). A total of 240 patients who were RT-PCR positive were included in the study. Compared to patients with mild disease, those with moderate to severe disease had a significant higher levels of the markers except serum albumin(p<0.0001). Albumin was significantly lower in these patients. A significant association was also seen between these markers and the outcome of the disease. Those who expired or left against medical advice (LAMA) had a significant higher levels of D-dimer, IL-6, CRP, procalcitonin and LDH as compared to those who were cured. IL-6, D-dimer, LDH, CRP, Procalcitonin and albumin are really helpful in knowing the severity of the disease and in disease surveillance.